Taxes and Benefits: Two Distinct Options to Cheat on the State? - Martin Halla; Friedrich G. Schneider (Johannes Kepler University of Linz, Department of Economics, 2005)
Economists have studied many aspects of tax evasion. The vast literature has concentrated on the individual taxpayer's decision on avoiding taxes by underreporting income. However no comprehensive investigation of the individual taxpayer's decision on claiming unjustified subsidies (e. g. by underreporting income) exists so far. Employing Austrian survey data we show that the basic attitude towards avoiding taxes (tax morale) and claiming unjustified subsidies (benefit morale) have different determinants. Our applied econometric framework relaxes the often stated assumption of the exogeneity of income as an explaining variable of tax morale. Furthermore we find empirical evidence that tax morale and benefit morale have different impact on actual behavior: Whereas a low benefit morale leads indeed to unjustified claims on benefits and therefore to higher income, we find no statistically significant effect of tax morale on tax evasion. These different determinants and effects of tax morale and benefit morale can be explained by differences in the deterrence factors from the traditional economic approach, by alternative theories or simply by more opportunities to cheat on the state by unjustified subsidies in contrast to avoiding taxes.
Keywords: H20; H26; 330; tax; subsidies; tax morale; benefit morale; tax evasion; benefit fraud; Steuermoral; Steuervermeidung; Sozialhilfe; Schätzung; Österreich; Betrug